2018
DOI: 10.1186/s13098-018-0359-9
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic syndrome modifies the mRNA expression profile of extracellular vesicles derived from porcine mesenchymal stem cells

Abstract: BackgroundMesenchymal stem cells (MSCs) perform paracrine functions by releasing extracellular vesicles (EVs) containing microRNA, mRNA, and proteins. We investigated the mRNA content of EVs in metabolic syndrome (MetS) and tested hypothesis that comorbidities interfere with the paracrine functionality of MSCs.MethodsMesenchymal stem cells were collected from swine abdominal adipose tissue after 16 weeks of a low- (Lean) or high-calorie (MetS) diet (n = 5 each). We used next-generation mRNAs sequencing to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…This may in turn induce expression of genes encoding for several proinflammatory cytokines, impairing the immunomodulatory potential of MSCs in subjects with MetS. Indeed, we found that expression of the proinflammatory cytokines TNF-α, MCP-1 IL-6, and IL-1β was higher in renal tubular cells cocultured with MetS-EVs compared with cells untreated or cocultured with Lean-EVs, extending our previous observations [41]. Nevertheless, proliferation capacity of PK1 cells was unaltered following coincubation with either Lean-or MetS-EVs, arguing against major effect of these inflammatory pathways on proliferation of renal tubular cells.…”
Section: Discussionsupporting
confidence: 85%
“…This may in turn induce expression of genes encoding for several proinflammatory cytokines, impairing the immunomodulatory potential of MSCs in subjects with MetS. Indeed, we found that expression of the proinflammatory cytokines TNF-α, MCP-1 IL-6, and IL-1β was higher in renal tubular cells cocultured with MetS-EVs compared with cells untreated or cocultured with Lean-EVs, extending our previous observations [41]. Nevertheless, proliferation capacity of PK1 cells was unaltered following coincubation with either Lean-or MetS-EVs, arguing against major effect of these inflammatory pathways on proliferation of renal tubular cells.…”
Section: Discussionsupporting
confidence: 85%
“…We acknowledge several limitations to this study, including a modest number of samples and inability to identify MSC post-translational/epigenetic changes. MSC at the 3rd passage possess a phenotype comparable to their parent cells (51), and we have previously validated trends observed in RNAseq using PCR and Western Blots (17, 5155). Future studies will also need to define the functional limitations that MetS impose on MSC, and the mechanisms by which it modifies genetic and protein cellular information.…”
Section: Discussionsupporting
confidence: 57%
“…This is fairly plausible, considering that physiologically MSCs reside in niches characterized by a low oxygen tension (hypoxia), albeit inhibitory effects of hypoxia on the proliferative and differentiation abilities of MSCs have been demonstrated in vitro . In addition, exposing MSCs to different metabolic conditions, such as diabetes, which is a pathological condition predisposing to AD, can modify characteristics of the obtained EVs . Therefore it should be carefully considered that the in vitro and in vivo states of MSCs could determine different effectiveness of EVs.…”
Section: The Extracellular Environment Influences the Type Of Releasementioning
confidence: 99%